Twenty years of political transition - Daniel Treisman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
What explains the divergent political paths that the post-communist countries of Eastern Europe and the former Soviet Union have followed since the fall of the Berlin Wall? While some appear today to be consolidated democracies, others have all the features of consolidated autocracy. This study reviews the patterns of change and examines correlates of progress towards democracy. Variation across post-communist countries in the degree of democracy twenty years after the start of transition can be parsimoniously explained by two variables: the length of time the country spent under a communist regime and - within the former Soviet Union, but not Eastern Europe - the proportion of Muslim adherents in the population.
Keywords: P36; P26; O57; P48; 330; democracy; transition; post-communism; Islam